Characteristics of Ionospheric Irregularities Using GNSS Scintillation Indices Measured at Jang Bogo Station, Antarctica (74.62°S, 164.22°E) - Junseok Hong; Jong‐Kyun Chung; Yong Ha Kim; Jaeheung Park; Hyuck‐Jin Kwon; Jeong‐Han Kim; Jong‐Min Choi; Young‐Sil Kwak (Space Weather)
Abstract Global Navigation Satellite System (GNSS) signals strongly depend on the ionospheric conditions, which are composed of electrons and ions generated by solar radiation and particle precipitation. Ionospheric plasma irregularities may cause the scintillation of the GNSS signals or even the loss of signal lock, resulting in the reduction of positioning accuracy and timing precision. Phase scintillation phenomenon is known to occur frequently at high latitudes and primarily related to a significant plasma density gradient, which is due to fast plasma flows in the polar region, energetic particle precipitation in the auroral region, polar cap patches, or several instability mechanisms. Statistical studies are required to understand the characteristics of ionospheric (both phase and amplitude) scintillations at high latitudes. Here, we report the results of ionospheric scintillation measurements at Jang Bogo Station (JBS; 74.62°S, 164.22°E), located inside the polar cap region in Antarctica. The occurrence rates of ionospheric scintillations over the JBS are recorded for 2 years (2017–2018) during solar minimum conditions. The occurrence rates of amplitude scintillations increase only at lower elevation angles (below 30°), which are hard to determine whether the source is ionospheric irregularity or ambient noise such as multipath. In contrast, the occurrence rates of phase scintillations depend on the azimuth angle, season, magnetic activity, magnetic local time, and signal frequency. The results of our analysis suggest that users of the GNSS should consider these parameters to prepare for the degradation of the GNSS performance at high latitudes in the Southern Hemisphere.